A New Approach to Constrain Crustal Vp/Vs From Rayleigh Wave Phase Velocity and Local Amplification: Application to the Western US - Yiran Huang; Colleen A. Dalton; Anant Hariharan (Geophysical Research Letters)
Abstract The ratio of compressional‐ and shear‐wave velocities, Vp/Vs, in the continental crust is a useful proxy for silica abundance and partial melt. However, constraining crustal Vp/Vs remains challenging. Rayleigh wave site amplification is a valuable complement to phase velocity and can constrain crustal Vp. We develop a two‐step approach to jointly invert phase velocity and amplification for Vp/Vs in the crust and Vsv in the crust and uppermost mantle. We apply this joint inversion to construct new crustal Vp/Vs models for the western US from three different amplification data sets. The models contain Vp/Vs values in the range 1.6–1.85 and variations that are consistent between the three models and with previous results, including a westward increase of Vp/Vs across the Central Basin and Range. Crustal Vp/Vs across three regions of the Basin and Range are explored to gain insight into crustal composition and enhance understanding of crustal evolution.